Evaluation of Information Security Awareness on Digital Marketing (Case Study of MSME in Indonesia) - Ahmad Zamsuri,; Wenni Syafitri,; Eddis Syahputra Pane, (Advances in Humanities and Contemporary Studies, 2021)
Digital marketing allows more intensive interaction, especially getting personal information. The mechanism of digital marketing on social media is also experiencing evolution, like on Facebook. Facebook is the choice of companies and service providers, both large and small, as an advertising medium. This is because they quickly get customers. After all, ads will be displayed on the customer's Facebook homepage. This ease will pose many threats in the future. Therefore, the formulation of this research is how to evaluate information security awareness in digital marketing, especially at MSME.This study evaluates MSME in Indonesia but is constrained by the number of MSME participating. There were 384 MSME needed, but only 17 were collected—data processing using these data resulted in a reasonably good test on reliability, validity, and normality. When testing the validity, only a few variables are invalid, such as K15, K17, K9, K13, K1, K2, A12, A1, A2, B2, B3, B4, and B14. Overall valid variable items are 79.4%. In contrast, the reliability of each variable K, A, and B is reliable. However, for the data normality test, only the Attitude (A) variable has not been standard.